'It's kind of becoming a culture': how habitus influences the migration trajectories of African students in China. Issue 13 (3rd October 2022) - Mulvey, Benjamin; Mason, Mark
ABSTRACT: Global flows of international students have diversified in recent years. As a result, the common association of this form of mobility with affluent members of the global middle class increasingly does not hold. This study focuses on one emergent student migration pattern that has been the subject of relatively little empirical research: that of African international students in China. The main aim is to establish how international student migration is experienced differentially by students positioned in their home societies in unequal ways, thereby moving beyond the notion that international student migration is a middle-class activity. Drawing on data from semi-structured interviews with 40 students from 14 African countries, we apply Bourdieu's theory of practice to examine the extent and nature of habitus transformation of students from a variety of social backgrounds. We show that differences in social background in this particular case led to distinct trajectories during the sojourn and in terms of post-study plans. Our study makes a theoretical contribution to the international student migration literature, arguing that the nature of transformation that took place among student migrants as a result of study was shaped by the nature of mobility, both spatial and social.